Brand positioning in the pharmaceutical industry: content analysis applied to antiaging drugs - Brizolla, Natasha (2017)
Under the shifting dynamics of pharmaceutical industries, companies must be responsive to adjust their strategies to the constantly evolving environment as well as predict future changes to be able to prepare and position their brands in the market to foster a privileged place. The goal of this study is to examine brand positioning strategies of age-related neurodegenerative drugs through content analysis in order to provide an overview of the pharmaceutical industry strategic approach regarding marketing and communication initiatives. This research adopted a descriptive qualitative methodology and begun by exploring concepts and theories regarding brand positioning and its application in the industry at hand. Then data was collected and examined under the Costumer-Driven Positioning framework from Vanderveer & Pines (2007) that focuses on physicians and message construction according to five rubrics: problem statement, functional benefits, main theme, emotional benefits, and reasons to believe. This research assessed each rubric of the CDP model and applied them for the eight brands embracing three major disease groups: Alzheimer, Parkinson, and Amyotropic Lateral Sclerosis. Suggestions of additional elements to be incorporated as well as limitations to be further investigated were discussed at last.